Relationship marketing orientation to improve the quality of service applied research in some Iraqi mobile phone companice - جثير, سعدون حمود; فيصل, شروق جاسم (Journal of Economics and Administrative Sciences, 2017)
This research is based on  interaction of two most important variables to the business organizations in the current era ,  these two variables are (marketing orientation and quality of service),  this research is trying to urge the service organizations to reconsider the mechanisms adopted in the formulation of its plans, It was the application of research in Korek Telecom and Asia Cell Telecom as a sector of service active and important in the business sector in Iraq, the information was obtained through the design of the Likert questionnaire , it was distributed (92) questionnaire , (50) for the company Korek Telecom and (42) of the Asia-Cell and represent research population sample included a number of staff in the departments and units in the two companies , the questionnaire was supported with the help of interviews and observation were formulating President hypothesis for research, The researcher used a number of statistical methods and descriptive is, the arithmetic mean, standard deviation, variance, coefficient of variation, simple correlation coefficient based on SPSS , The researcher reached to the group's conclusions most notably the a correlation relationship between marketing orientation and quality of service, and the most prominent recommendations that concluded by the research was about the necessity companies focus their efforts in the development- marketing orientation through to pay attention and focus on providing quality service and take into consideration the activities relating to the provision of service.